2017
DOI: 10.1108/arla-05-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

Family business and value-added distribution: a socioemotional wealth approach

Abstract: Purpose Research has demonstrated that family businesses limit the goal of maximizing profits in exchange for maintaining control of the company and passing control to future generations. However, these decisions are not always shared by the stakeholders who are outside the family context, making tensions arise within the company that may affect profitability and the share prices of the family business. The purpose of this paper is to analyse the internal tensions in family businesses in the value-added (VA) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
9
0
8
Order By: Relevance
“…These results suggest that family CEOs prefer self-financing, a preference that is justified by their greater apparent risk aversion and prioritizing maintaining control over the company. This behavior by family CEOs is in line with behavior that is traditionally associated with family businesses, i.e., they prefer to finance with their own family money (Gallizo, Mar-Molinero, Moreno & Salvador, 2017b;Hamilton & Fox, 1998;Romano, Tanewski, & Smyrnios, 2000) or with undistributed profits (Hamilton & Fox, 1998;Barton & Matthews, 1989) instead of using debt or bringing on new shareholders. On the contrary, the results obtained for non-family CEOs show evidence of their preference for taking on debt, a practice that is more in line with non-family businesses.…”
Section: Return On Assetssupporting
confidence: 63%
“…These results suggest that family CEOs prefer self-financing, a preference that is justified by their greater apparent risk aversion and prioritizing maintaining control over the company. This behavior by family CEOs is in line with behavior that is traditionally associated with family businesses, i.e., they prefer to finance with their own family money (Gallizo, Mar-Molinero, Moreno & Salvador, 2017b;Hamilton & Fox, 1998;Romano, Tanewski, & Smyrnios, 2000) or with undistributed profits (Hamilton & Fox, 1998;Barton & Matthews, 1989) instead of using debt or bringing on new shareholders. On the contrary, the results obtained for non-family CEOs show evidence of their preference for taking on debt, a practice that is more in line with non-family businesses.…”
Section: Return On Assetssupporting
confidence: 63%
“…Research has found that "family businesses limit the goal of maximizing profits in exchange for maintaining control of the business and passing that control on to future generations" [46]. In addition to economic ownership, FFs have affective values that influence the succession process; these family business values have been grouped under the concept of socioemotional wealth.…”
Section: The Relationship Between Intention Of Potential Successors and Socioemotional Wealth (Sew)mentioning
confidence: 99%
“…Although different articles have been recently developed linking the SEW approach with diverse areas of knowledge, such as business management (Gallizo et al , 2017; Schulze, 2016), diversification (Gómez-Mejía et al , 2007; Gómez-Mejia et al , 2010), business valuation (Zellweger and Dehlen, 2012), performance (Cruz et al , 2012; Martínez-Romero and Rojo-Ramírez, 2017; Rojo-Ramírez and Martínez-Romero, 2018) and innovation (Filser et al , 2018; Gast et al , 2018; Hauck and Prügl, 2015), more research is needed regarding the role SEW plays in family firms’ TI.…”
Section: Theoretical Foundationsmentioning
confidence: 99%